Determining of Efficiency For The N749 Dye contact with TiO2 In Dye Sensitized Solar Cell - Nahi, Naeam; Hadi J. M. Al-Agealy; Hossain Milani Moghaddam (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2024)
In this research, we investigate and evaluate the efficiency of a hetero junction N749-  device based on a simple donor-acceptor model for electron transfer. Electron transfer from a photo-excited N749 sensitized into a wide-band gap  is the basic charge separation in dye-sensitized solar cells, or "DSSCs". Due to the understanding of the current of the DSSCs functioning mechanism, the energy levels of the hetero junction N749-  device surrounded by DCM solvent as polar media must be continuum levels. The current-voltage (J-V) characteristics of the N749- device are calculated in two concentrations at room temperature (T=300 k) and 100   irradiation. The fill factor and efficiency of the device are found to be 0.134 and 6.990 for concentration  compared to 0.146 and 9.974 for concentration . The efficiency of the N749-  device is in agreement with experimental results. It also offers a rational for the suggestion to use the application of N749-  high-performance solar cells.